CDM mechanisms-based modelling of tertiary creep: ability to predict the life of engineering components (Archives of Mechanics - Test, 2005)
The paper demonstrates how computational CDM can be used to predict the behaviour of structural components, ranging from modest stress concentrators to the growth of cracks by creep. Size effects in CDM analysis are addressed, and it is shown how a non-local CDM approach can be used to predict the observed crack tip behaviour. The proviso being that the length scales, associated with the damage fields and gradients, be modelled to comply with continuum theory. It is shown how damage state variable theories may be used to provide traceability from the physics of micro-mechanisms to the macro-material behaviour described by constitutive equations. The paper presents a detailed analysis of creep rupture in ferritic steel weldments, and shows how multi-axial stress rupture criteria, weldment phase dimensions, and constitutive equations for each material phase of the weld, can be used in Finite Element CDM analyses to predict the results of experiments carried out on butt-welded pipes and cross-welded tension testpieces. Original results are presented which show how the above CDM techniques have been used to perform a three-dimensional CDM high-temperature creep rupture analysis of a welded cylinder-cylinder pressure vessel intersection; and, to predict damage initiation and crack growth. The paper also demonstrates how CDM conservatively predicts the vessel lifetime; and, how the experimentally observed weld failure mechanism is well predicted.